Genomic analysis of Arthrobacter endolithicus sp. nov. and Arthrobacter antibioticus sp. nov., two novel actinobacteria from Antarctica with potential application in aquaculture - Ay, Hilal; Sahin, Sibel Melisa; Saticioglu, Izzet Burcin; Duman, Muhammed (SPRINGER, 2025)
In this study, we aimed to discover and characterize novel Antarctic actinobacteria with potential probiotic benefits for aquaculture, emphasizing their taxonomy, antimicrobial properties, and adaptability to aquaculture environments. Strains H14-L1T and H35-MC1T, were isolated from rock samples collected in Horseshoe Island, Antarctica. The strains showed antimicrobial activity against several common fish pathogens, i.e. Aeromonas hydrophila ATCC 7966 T, A. hydrophila Ah-2, A. sobria A-sor2, A. sobria ATCC 43979 T, Vibrio anguillarum NCIMB6T and V. anguillarum Va-2, and compatibility with the aquaculture conditions. A combination of phenotypic, chemotaxonomic, and whole-genome analyses was conducted to classify the strains and assess their potential as probiotics. The pairwise comparison of 16S rRNA genes of both strains revealed that the strains were members of the genus Arthrobacter, with the highest pairwise identity values calculated as 99.6% for strain H14-L1T and 'A. terrae' Z1-20 T, 99.1% for strain H35-MC1T and A. polaris C1-1 T. However, the overall genome-relatedness indices confirmed that both strains were novel species within the genus Arthrobacter. The chemotaxonomic characterization for polar lipids showed that both strains contained diphosphatidylglycerol, phosphatidylglycerol, phosphatidylinositol and an unidentified glycolipid. In addition, the strains contained galactose, glucose, ribose, and trace amounts of rhamnose in their whole-cell sugar hydrolysates. The comprehensive annotation of the genomes for secondary metabolite-coding gene clusters revealed that both strains have genes for terpenes, polyketides and putatively bioactive peptides. The strains exhibited bile tolerance, a moderate level of hydrophobicity and no haemolysis in terms of compatibility with aquaculture conditions. In conclusion, both strains-proposed as Arthrobacter endolithicus sp. nov. and Arthrobacter antibioticus sp. nov.-demonstrated promising probiotic traits and antimicrobial activity, underscoring their potential as novel biocontrol agents in aquaculture. Future in vivo validation and safety assessments are required to confirm their efficacy and facilitate their application in sustainable fish farming.
Keywords: Actinomycetota; Aquaculture; Bioactivity; Genomic analysis; Probiotics; BACTERIA; IDENTIFICATION; SEQUENCES; TAXONOMY; DATABASE; CLUSTER; ARTS; Microbiology